2020
DOI: 10.5194/gmd-2020-307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Schwarz iterative method to evaluate ocean- atmosphere coupling schemes. Implementation and diagnostics in IPSL-CM6-SW-VLR

Abstract: Abstract. State-of-the-art Earth System models, like the ones used in the CMIP6 intercomparison project, suffer from temporal inconsistencies at the ocean-atmosphere interface. Indeed, the coupling algorithms generally implemented in those models do not allow for a correct phasing between the ocean and the atmosphere, and hence between their diurnal cycles. A possibility to remove these temporal inconsistencies is to use an iterative coupling algorithm based on Schwarz methods. Despite the fact that the comput… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Such 1D coupled configurations are particularly relevant to perform studies related to the time coupling schemes. It is a very practical tool to test new approaches like Schwartz methods that enable correcting the mismatch in between components due to asynchronous coupling through an iterative method (Marti et al, 2020) and to assess the effect of different coupling algorithms from purely sequential to asynchronous. It is also an interesting tool to assess the effect of surface flux parameterizations on both ocean and atmospheric boundary layers.…”
Section: Discussionmentioning
confidence: 99%
“…Such 1D coupled configurations are particularly relevant to perform studies related to the time coupling schemes. It is a very practical tool to test new approaches like Schwartz methods that enable correcting the mismatch in between components due to asynchronous coupling through an iterative method (Marti et al, 2020) and to assess the effect of different coupling algorithms from purely sequential to asynchronous. It is also an interesting tool to assess the effect of surface flux parameterizations on both ocean and atmospheric boundary layers.…”
Section: Discussionmentioning
confidence: 99%
“…[22] suggested that the convergence is insensitive to variations of ν j (z) at large frequencies. Indeed, in the ω → ∞ limit, regardless of the viscosity profile, the S 1 S 2 product, with S j defined in either (28), (30), or (34), converges towards the same value…”
Section: Behaviour Of the Convergence Rates With Dn Transmission Conditionsmentioning
confidence: 92%
“…for the so-called shallow-water equations [31,36], or for the ocean primitive equations [1]. At a more practical level, the dynamical core of at least one Earth system numerical model relies on a SWR algorithm for its domain decomposition method [35], and empirical studies have been undertaken for including Schwarz methods in ocean -atmosphere couplers [30]. Generally speaking, the theoretical convergence analysis of SWR algorithms is restricted to relatively simple linear model problems, often approximating space-varying quantities as constant coefficients, assuming that scalar variables are independent from each other, so that all the conditions to apply Fourier and Laplace transformations are met.…”
Section: Context and Motivationsmentioning
confidence: 99%